Tantangan Pembelajaran IPS dalam Pembelajaran Inovatif - Laila, Masayu; Desfianti, Safina; Amanullah, Rakha agusti; Safitri, Sani (Bersatu: Jurnal Pendidikan Bhinneka Tunggal Ika, 2025)
Social studies (IPS) learning is very important to provide students with the knowledge and skills needed to understand the social, cultural, economic, and political dynamics that occur in society. However, in an era of ever-evolving education, IPS learning faces various challenges, especially in the application of innovative learning. This article discusses the main challenges faced in the implementation of innovative IPS learning, such as limited resources, lack of curriculum flexibility, and teaching methods that are less in line with current developments. The use of technology in IPS learning is an issue that needs attention, considering that there are still many teachers who do not have optimal skills in utilizing technology. To overcome this problem, educators must change their way of thinking, get good training, and provide appropriate facilities and infrastructure. With an innovative learning approach in IPS, students are not only taught material but also taught modern skills such as creativity, critical thinking, and collaboration. These skills are very important for designing students to solve problems around the world.